The efficacy of polymyxin B in treating stroke-associated pneumonia with carbapenem-resistant Gram-negative bacteria infections: a multicenter real-world study using propensity score matching - Zhuang, Hai-Hui; Chen, Qi-Hua; Wang, Wei; Qu, Qiang; Xu, Wei-Xin; Hu, Qin; Wu, Xiao-Li; Chen, Ying; Wan, Qing; Xu, Tian-Tian; Long, Wen-Ming; Luo, Yue; et al. (Frontiers in Pharmacology, 2025)
ObjectivesInfection with Carbapenem-resistant Gram-negative bacteria (CR-GNB) poses further challenges in treating stroke-associated pneumonia (SAP) patients. This multicenter retrospective study aimed to evaluate the efficacy of polymyxin B (PMB) in CR-GNB-infected SAP patients and to identify factors that may influence its effectiveness.MethodsFrom 1 September 2019, and 30 December 2022, a total of 196 CR-GNB-infected SAP patients from five hospitals in China were included in the study based on specific criteria. Demographics and clinical data were obtained from the electronic medical records. Propensity score matching (PSM) was used to minimize the effect of potential confounding variables. Univariate analysis and multivariate logistic analysis were performed to identify risk factors affecting microbial efficacy.ResultsAmong the 196 SAP patients infected with CR-GNB, 24.5% received PMB combined inhalation and 75.5% received non-combined inhalation treatment. The clinical success rate was 68.9%, with 25.5% achieving microbial efficacy within 7 days and 37.8% achieving microbial cure. The 30-day all-cause mortality rate was 14.8%. The incidence of acute kidney injury was 34.7%. After adjustment by propensity score matching, the PMB combined inhalation group exhibited significantly higher microbial efficacy compared to the non-combined inhalation group (46.7% vs. 26.7%, p = 0.049). Multivariate logistic analysis identified multi-site infections and Carbapenem-resistant Pseudomonas aeruginosa infection as independent risk factors for microbial efficacy.ConclusionCombined inhalation of PMB demonstrated superior effectiveness in microbial clearance compared to non-combined inhalation in treating CR-GNB-infected SAP patients. We recommend aerosol combined inhalation of PMB and suggest developing personalized PMB-based regimens for individual patients to enhance treatment outcomes.